2020
DOI: 10.1038/s41467-020-19603-1
|View full text |Cite|
|
Sign up to set email alerts
|

Recent evolution of a TET-controlled and DPPA3/STELLA-driven pathway of passive DNA demethylation in mammals

Abstract: Genome-wide DNA demethylation is a unique feature of mammalian development and naïve pluripotent stem cells. Here, we describe a recently evolved pathway in which global hypomethylation is achieved by the coupling of active and passive demethylation. TET activity is required, albeit indirectly, for global demethylation, which mostly occurs at sites devoid of TET binding. Instead, TET-mediated active demethylation is locus-specific and necessary for activating a subset of genes, including the naïve pluripotency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 218 publications
(339 reference statements)
3
53
0
Order By: Relevance
“…Early studies showed that PGC7 protects DNA methylation pattern during early embryogenesis via inhibition of TET2/TET3 [80,81]. Recently, however, it has been reported that PGC7, on the contrary, functions as a negative regulator of UHRF1/DNMT1-dependent DNA methylation by interacting with the PHD domain of UHRF1 [82][83][84]. Analysis of tissue microarray comprising 107 pairs of HCC tissues from human patients and their non-tumor counterparts revealed that PGC7 expression was significantly upregulated in advanced stage tumors and PGC7 positive cells were associated with poor clinical outcome.…”
Section: Inhibition Of Dnmts In Cancermentioning
confidence: 99%
“…Early studies showed that PGC7 protects DNA methylation pattern during early embryogenesis via inhibition of TET2/TET3 [80,81]. Recently, however, it has been reported that PGC7, on the contrary, functions as a negative regulator of UHRF1/DNMT1-dependent DNA methylation by interacting with the PHD domain of UHRF1 [82][83][84]. Analysis of tissue microarray comprising 107 pairs of HCC tissues from human patients and their non-tumor counterparts revealed that PGC7 expression was significantly upregulated in advanced stage tumors and PGC7 positive cells were associated with poor clinical outcome.…”
Section: Inhibition Of Dnmts In Cancermentioning
confidence: 99%
“…It was demonstrated that the underlying reason for such low methylation was impaired UHRF1 activity (von Meyenn et al, 2016 ). While initially UHRF1 was shown to be unstable at the post-translational level in 2i ESCs (von Meyenn et al, 2016 ), subsequently it was demonstrated that DPPA3 is the factor that is impeding UHRF1 function (Mulholland et al, 2020 ). Through a rigorous set of biochemical and microscopy-based experiments, Mulholland et al showed that DPPA3 binds to UHRF1, thus impairing the latter's ability to bind to chromatin ( Figure 1 ).…”
Section: Passive Aggressive: Dna Demethylation After Fertilizationmentioning
confidence: 99%
“…Finally, Mulholland et al showed that TET1 and TET2 are required for demethylation of Dppa3 regulatory regions, thus its activation ( Figure 1 ) (Mulholland et al, 2020 ). In other words, targeted demethylation of one gene supports global passive demethylation.…”
Section: Passive Aggressive: Dna Demethylation After Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Remaining masks were then used to measure intensity of Lin28A inside the nucleus. To measure intensity in the cytoplasm, we enlarged the masks by 3 pixels, and took the intensity along the perimeter of the enlarged mask as a readout for intensity in the cytoplasm (discarding pixels which lay in neighbouring masks), similarly to cytoplasm intensity measurements carried out elsewhere (Mulholland et al, 2020) .…”
Section: Cytoplasm and Nucleus Intensity Analysismentioning
confidence: 99%